A boa expressão ao cantar ou tocar: tradução comentada do Versuch Einer Anweisung Die Flöte Traversiere Zu Spielen de Quantz (extratos). - Rezende, Renan Felipe Santos (2015)
The proposal of this dissertation is a critical translation of five extracts from the Versuch einer Anweisung die Flöte traversiere zu spielen (essay of a method to play the flute), by Johann Joachim Quantz, published in Berlin in 1752. This work presents essential questions about the German Flute Technique and about the instrumental practices from the eighteenth century. It’s importance and influence is justified by it’s widely dissemination over the centuries after many different editions and translation to many languages form German to Japanese. Translate this work to Portuguese turn it possible the access of a Brazilian student to a fundamental primary fount of information about the musical practices of the eighteenth century. This translation was made from a compilation of the French (1752), the English (2001) and Spanish (2007) editions. For the comments, it was tried to do an immanent reading with the purpose of unveil the categorical connections the influenced Quantz in the construction of his technical and musical ideas. This reading embraced a aesthetical, historical and musical analysis of some specific parts of the treaty, based, mainly, on the technical and musical concepts of Taffanel e Gaubert (1958) and Henry Altès (1880), and on the historical and aesthetical perspectives of Enrico Fubini (1970, 2008) and Nikolaus Harnoncourt (1998). It can be understood then that the music and/or the flute learning, specifically, demands the development of a technique that can be only achieved through a widely human formation that could unite practical knowledge and academic formation, experience and knowledge. Music by Quantz aims to move human trough a sound that is based in expression, ideal the music can be made from sensitive and affective melodic conduction.